1999
DOI: 10.1046/j.1365-2133.1999.02777.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of latent Epstein?Barr virus infection with hydroa vacciniforme

Abstract: Patients with hydroa vacciniforme (HV)-like eruptions and malignant potential have been reported from Asia and Mexico, and those patients frequently had an associated latent Epstein-Barr virus (EBV) infection. In order to elucidate the association of latent EBV infection with HV, we studied six children with typical manifestations of HV by detection of EBV genes and EBV-related RNAs in biopsy specimens from cutaneous lesions. Cutaneous lesions of all six children with typical HV contained EBV-encoded small nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 24 publications
3
98
0
1
Order By: Relevance
“…Some patients lack abnormal patterns of EBV-related antibodies, whereas other patients lack major organ involvement and have only skin symptoms, such as hypersensitivity to mosquito bites (HMB) or hydroa vacciniforme-like eruptions. 10,11 On the other hand, we and others have reported patients with CAEBV infection had extremely high viral loads, as assessed by quantitative polymerase chain reaction (PCR). 12,13 Moreover, accumulating evidence suggests that clonal expansion of EBV-infected T or natural killer (NK) cells could be associated with CAEBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients lack abnormal patterns of EBV-related antibodies, whereas other patients lack major organ involvement and have only skin symptoms, such as hypersensitivity to mosquito bites (HMB) or hydroa vacciniforme-like eruptions. 10,11 On the other hand, we and others have reported patients with CAEBV infection had extremely high viral loads, as assessed by quantitative polymerase chain reaction (PCR). 12,13 Moreover, accumulating evidence suggests that clonal expansion of EBV-infected T or natural killer (NK) cells could be associated with CAEBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the atypical form presents with fever, liver dysfunction, edematous swelling of the face, unusual skin lesions, and progression to subcutaneous lymphoma accompanied by HPS. 6 On the strength of these findings, we have proposed that EBV-associated T/NK-cell LPD is a distinct disease entity. 2,8 These diseases occur at any age and in both sexes.…”
mentioning
confidence: 99%
“…Subsequently, EBV-associated T/NK-cell LPD was linked to EBV-associated hemophagocytic syndrome (EBV-HPS), peripheral T-cell leukemia, aggressive NK-cell leukemia and nasal/nasal-type NK-cell lymphoma. 2 More recently, Ishihara et al 5 reported a close relationship between hypersensitivity to mosquito bites and EBV-associated NK-cell LPD, while Iwatsuki et al 6 showed that hydroa vacciniforme was characterized by the infiltration of EBV-infected T-cells. Despite their heterogeneity, the diseases associated with EBV-infected T/NK-cells generally have a poor outcome.…”
mentioning
confidence: 99%
“…In addition, the relation of HV with EBV has been emphasized in recent years (4, 6). Iwatsuki et al (6) showed the presence of small nuclear ribonucleic acid (EBER) cells which are coded by EBV in skin involvement in 6 patients with clinical and histological typical HV. In addition, they proposed that typical and atypical HV were the forms included in the same disease spectrum as EBV-related lymphoproliferative diseases.…”
Section: Discussionmentioning
confidence: 99%